2016
DOI: 10.1186/s12245-016-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

Unusual side effect of cannabis use: acute abdomen due to duodenal perforation

Abstract: Background: The chronic use of synthetic cannabinoids (SCs) which has become an increasingly prevalent problem can rarely cause gastric and duodenal ulcer because of their effects on gastric secretion and emptying. Since peptic ulcer disease (PUD) is a rarely seen entity in patients who consult to the emergency service with complaints of abdominal pain, most of the physicians do not suspect of this clinical diagnosis. Perforation is a mortal complication of PUD, and early diagnosis and emergency surgery are li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The specific gastrointestinal lesions in subjects with chronic cannabinoid consumption are due to a chronic delay in gastric emptying and consist of ischemia and peptic ulcer disease reported as single cases in the literature. 30 , 31 Interestingly, H. pylori infection is one of the predisposing factors to peptic ulcer disease. Thus, H. pylori could represent the mechanism underlying the development of peptic ulcer disease in individuals with chronic cannabinoid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The specific gastrointestinal lesions in subjects with chronic cannabinoid consumption are due to a chronic delay in gastric emptying and consist of ischemia and peptic ulcer disease reported as single cases in the literature. 30 , 31 Interestingly, H. pylori infection is one of the predisposing factors to peptic ulcer disease. Thus, H. pylori could represent the mechanism underlying the development of peptic ulcer disease in individuals with chronic cannabinoid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gastrointestinal involvement was found as well. Buyukbese Sarsu described a young patient who developed duodenal perforation as a complication of a peptic ulcer disease, following chronic SC use [ 23 ]. Sevinc et al reported a very rare case of acute gastric dilatation (AGD) and hepatic portal venous gas (HPVG) with findings of acute abdomen resulting from chronic use of a SC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study done by Zhang P., Huang Y., Hao H., et al found that THC inhibited the migration of keratinocytes, which are the cells responsible for closing wounds. This study also found that THC decreased the production of collagen, which is necessary for wound healing and tissue repair [ 26 ].…”
Section: Reviewmentioning
confidence: 98%
“…Some studies have linked cannabis use with an increased risk of post-endoscopic retrograde cholangiopancreatography (ERCP)-induced pancreatitis [ 22 , 24 , 25 ]. Studies show that people under age 35 who use cannabis recreationally or for certain medical reasons are at increased risk for pancreatitis [ 22 , 23 , 26 , 27 ]. Although most studies show an increased overall incidence of AP with cannabis use, some other studies have documented improved outcomes in AP patients using cannabis when compared to non-users.…”
Section: Reviewmentioning
confidence: 99%